Endometrial thickness cut-off value by transvaginal ultrasonography for screening of endometrial pathology in premenopausal and postmenopausal women - Park, Yu Ran (Obstet Gynecol Sci, 2019)
OBJECTIVE: To assess the clinical usefulness and diagnostic accuracy of ultrasonographic measurement of endometrial thickness (ET) in women with endometrial hyperplasia or cancer (EH+). METHODS: This retrospective cohort study included 29,995 consecutive women who underwent transvaginal ultrasonography (TVS) for an incidental finding of a thickened endometrium at the health screening and promotion center at Asan Medical Center between 2006 and 2010. Among 959 patients with endometrial abnormalities, 92 patients were included in this study. A total of 867 patients were excluded: 416 were lost to follow-up; 263 did not undergo endometrial biopsy; 155 had endometrial polyps; 17 had submucosal myomas; and 16 had insufficient tissue samples. Endometrial histology was the reference standard for calculating accuracy. RESULTS: Of the 92 patients, 78 (84.8%) had normal pathology, while 14 (15.2%) had endometrial pathology (EH+), including 5 patients (35.7%) with simple hyperplasia without atypia, 3 (21.4%) with complex hyperplasia, and 6 (42.9%) with endometrial carcinoma, all stage Ia. The area under the receiver-operating characteristic curve was 0.75 (95% confidence interval [CI], 0.593–0.906). The cut-off value for ET was 8 mm, indicating that TVS ET had a fair accuracy in diagnosing carcinoma, had a sensitivity of 100% (95% CI, 62.9–100.0%) and a specificity of 24.3% (95% CI, 15.2–36.3%). CONCLUSION: TVS is useful for detecting EH+, with a cut-off value for ET of 8 mm having a high sensitivity for detecting endometrial pathologies and the ability to identify women highly unlikely to have EH+, thereby avoiding more invasive endometrial biopsy.